Rediscovering a legacy of a lost voice a history of Radyo DZLB's school-on-the-air - Chico, Mark Lester M. (2021)
The school-on-the-air (SOA) is a pioneering broadcast program developed by Radyo DZLB in the University of the Philippines Los Baños, Laguna, Philippines. Its history dates back to 1967 when the first SOA and dairy farming was launched. Over the years, SOAs were redesigned until a formal structure was arrived at. Radyo DZLB faced challenges that compelled SOA continuously find its rightful place in the airwaves. Now that it is off the air, how can Radyo DZLB sustain its advocacy of educating farmers, homemakers, and children, among others, through SOA? As the voice development, how can Radyo DZLB recover its lost voice? Employing a social history approach to writing media history, this article aims to record and critique the accounts of key informants and written historical facts from documentation in order to contribute to the ongoing history of educational broadcast in the Philippines, particularly of SOA, that is somehow making a "comeback" due to the demands of pandemic-stricken educational system. It would serve as a prelude to another rebirth of Radyo DZLB, whose tower has recently been built, and a new transmitter coming way soon.
Keywords: Radyo DZLB (Radio Station); Radio broadcasting